The Hidden Paradises: Geology and Geotourism Potentials in Lambu District, West Nusa Tenggara - Sayidatina Hayatuzzahra; Septyo Uji Pratomo (International Journal of Geotourism Science and Development, 2024)
Lambu District of Bima Regency, West Nusa Tenggara Province has three extraordinary geological features that can potentially be developed into geotourism objects: Pulau Kelapa, Tanjung Meriam, and Pantai Pink. These three objects can be accessed by water transportation. Pulau Kelapa is a geomorphological feature in the form of crescent-shaped hills. The land use as savanna with views of small island cluster resulted from volcanic activities, and can be observed from the top of the hills. Tanjung Meriam forms a headland morphology protruding towards the beach, composed of andesitic-basaltic igneous rocks in the form of columnar joints that extended spectacularly along the coastline. Tanjung Meriam is said to be the only largest columnar joint site in Indonesia that is still pristine and does not undergo any shape changes by human activities. The pink color of the sand at Pantai Pink is caused by the pigment of decomposed foraminifers that formed sand grains stretching along the beach area. In addition, the clean and clear sea water complements the beauty and aesthetics of the beach. Geologically, the area is made of by the Layered Limestone Formation (Tml) and Old Volcano Products (QTvs). Geomorphosite assessment for geotourism purpose, according to Kubalikova (2013), showed that the feasibility value of Pulau Kelapa, Tanjung Meriam and Pantai Pink is 57.91%, 51.66% and 51,66% respectively. Tourism development in this area is still limited to individual visits; yet to be managed further by the local government while at the same time the potential is enormous. Therefore, planning is needed to develop geotourism potential by considering scientific and educational (geology, biology and local culture) and tourism values for sustainable development